2019
DOI: 10.2147/ott.s200261
|View full text |Cite
|
Sign up to set email alerts
|

<p>Retinoic acid receptor &alpha; facilitates human colorectal cancer progression via Akt and MMP2 signaling</p>

Abstract: Purpose: Retinoic acid α (RARα) is overexpressed in various tumors and facilitates cancer progression. Although RARα has been shown to facilitate colorectal cancer (CRC) progression, more efforts to characterize mechanisms of RARα in CRC are needed in order to develop better target-based drugs for tumor therapy. Methods: RARα expression in CRC was assessed by IHC. EdU, QPCR, Western blotting, dual-luciferase reporter assay and ChIP were performed to explore the role of RARα i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Most of the aforementioned DMR regulated genes were not previously discovered for EPN relapses. Their potential as relapse driver genes was further enhanced by the fact that many of them, including CACNA1H 56 , SLC12A7 57 , CSPG4 58 , 59 , RARA 60 in RELA , and HSPB8 61 , ITGB4 62 , FAT1 63 , 64 in PFA tumors, have previously been associated with human cancers or ependymoma tumor dependency gene ( CACNA1H ) 11 , 65…”
Section: Resultsmentioning
confidence: 99%
“…Most of the aforementioned DMR regulated genes were not previously discovered for EPN relapses. Their potential as relapse driver genes was further enhanced by the fact that many of them, including CACNA1H 56 , SLC12A7 57 , CSPG4 58 , 59 , RARA 60 in RELA , and HSPB8 61 , ITGB4 62 , FAT1 63 , 64 in PFA tumors, have previously been associated with human cancers or ependymoma tumor dependency gene ( CACNA1H ) 11 , 65…”
Section: Resultsmentioning
confidence: 99%
“…Xiang et al 32 found that the ERα-36-STAT3 complex could directly bind to the promoter regions of MMP2/9 and promote their expression in breast cancer cells. In another study, ChIP analyses indicated that MMP2 transcription was directly regulated by RARα 33 . We revealed in this study that ELTD1 could activate the luciferase activity of MMP2 in CRC cells.…”
Section: Discussionmentioning
confidence: 94%
“… 24 Moreover, changes in MMP2 expression are related to the occurrence and development of CRC. For example, retinoic acid α promotes CRC carcinogenesis by increasing MMP2 transcription, 25 and seven transmembrane domains containing 1 (ELTD1/ADGRL4) can promote CRC cell migration and invasion by activating MMP2 at the transcriptional level. 11 Furthermore, TWIST1/2 can bind to the MMP2 promoter and induce its expression, resulting in increased epithelial-to-mesenchymal transition and invasion potential of CRC cells.…”
Section: Discussionmentioning
confidence: 99%